Molecular Diagnosis of Hymenolepis nana Parasite in House Rats and Children in Babylon Province, Iraq - Al-Talla, Dyaa H.A.; Al-Bermany, Safaa M.K. (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2024)
Background: Hymenolepiasis in humans is typically caused by the dwarf tapeworm Hymenolepis nana, or occasionally by the rodent tapeworm Hymenolepis diminuta. The current study aimed to detect and Hymenolepis nana infecting Children and House rate using molecular techniques. Methods: Seventy five samples of Children and seventy five of House rats were examined from December 2023 to March 2024 by the molecular techniques. Results: The results showed that the overall percentage of Hymenolepis nana infection was 13.3 (10 out of 75) in (Children) (female 31 and male 44) and in House rats was 16% (12 out of 75). These results also found that the infected males recorded the highest infection rate compared with infected females, where the percentages were (Children) male 10.9% (7/44) and female 9.7% (3/31), and (House rats) respectively. In addition, 75 stool samples of humans (children) in different areas (Al- Qasim, Al- Musayyib, Al- Hilla, Al- Kifl, Al- Hamza Al- Gharbi, and Al- Shomali) and study the effects of sex and areas with ages in humans. The infection rates of Hymenolepis parasite in humans by using molecular, the study revealed in humans on the infection rates by molecular. In humans H. nana was showed an infection rate 13.3% (10/75), the high infection rate was 20% (2/10) in Al Musayyib and 12.5% (1/8) in Al Kifl and it was 5.9% (1/17) in Al- Qasime with no significant difference, 20% (2/10) in Al- Hamza Al Gharbi, and 10% (1/10) in Al Shomali. Conclusion: The results were showed the parasite H. nana of the infected humans in this study tack three gropes (1-5) years about 20% (5/25), (6-10) years, 9.4% (3/32) and (11-15) years 11.1% (2/18).